2014
DOI: 10.1089/ten.tea.2013.0573
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Acellular Porcine Pulmonary Valve Scaffolds for Tissue Engineering

Abstract: Currently available replacement heart valves all have limitations. This study aimed to produce and characterize an acellular, biocompatible porcine pulmonary root conduit for reconstruction of the right ventricular outflow tract e.g., during Ross procedure. A process for the decellularization of porcine pulmonary roots was developed incorporating trypsin treatment of the adventitial surface of the scraped pulmonary artery and sequential treatment with hypotonic Tris buffer (HTB; 10 mM Tris pH 8.0, 0.1% (w/v) E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 38 publications
(41 reference statements)
5
47
1
1
Order By: Relevance
“…Tensile tests were performed using an Instron 3365 materials testing machine (Instron, Bucks, UK) fitted with a 50 N load cell. A strain rate of 10 mm/min was used, similar to that previously reported in studies of human thoracic aorta (Duprey et al, 2010), mitral valve tissue (Kunzelman and Cochran, 1992) and porcine pulmonary valve tissue (Luo et al, 2014). The samples were hydrated using phosphate buffered saline solution (PBS; MP Biomedicals, LLC) maintained at 37°C.…”
Section: Biomechanical Performance Ii: Materials Properties (Uniaxial mentioning
confidence: 99%
See 4 more Smart Citations
“…Tensile tests were performed using an Instron 3365 materials testing machine (Instron, Bucks, UK) fitted with a 50 N load cell. A strain rate of 10 mm/min was used, similar to that previously reported in studies of human thoracic aorta (Duprey et al, 2010), mitral valve tissue (Kunzelman and Cochran, 1992) and porcine pulmonary valve tissue (Luo et al, 2014). The samples were hydrated using phosphate buffered saline solution (PBS; MP Biomedicals, LLC) maintained at 37°C.…”
Section: Biomechanical Performance Ii: Materials Properties (Uniaxial mentioning
confidence: 99%
“…Numerous types of detergents and biological agents have been used for decellularisation with varying concentrations, including SDS Luo et al, 2014), trypsin (Liao et al, 2008), EDTA (Liao et al, 2008;Paniagua Gutierrez et al, 2015), Triton X-100 (Liao et al, 2008) (Jordan et al, 2012) and hypertonic solutions (Jordan et al, 2012). It has previously been reported that decellularisation treatment can introduce changes in the tissue structure, which may influence the mechanical properties of the tissue Spina et al, 2003;Gilbert et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations